An uncertainty-based structural design and optimization method with interval Taylor expansion. (October 2021) - Meng, Debiao; Hu, Zhengguo; Guo, Jinbao; Lv, Zhiyuan; Xie, Tianwen; Wang, Zihao
Abstract: There are uncertain factors affecting structural performance in actual engineering. The uncertainty-based design and optimization (UBDO) is an effective strategy to deal with these uncertain factors and improve the reliability of structural systems. In UBDO, some non-probabilistic uncertainties are difficult to be described with a certain distribution information. In this situation, the interval uncertainty analysis (IUA) can be utilized to perform the reliability evaluation in UBDO. Generally, if IUA was performed directly in UBDO, the efficiency of UBDO with IUA (UBDO-IUA) cannot satisfy the requirements of actual engineering. To tackle this problem, in this study, an UBDO-IUA strategy based on the Taylor expansion is proposed. The particle swarm global optimization algorithm is also introduced in the given method as the optimization solver to further improve the computational efficiency. Two examples are introduced to show the utilization of the given method.